Cardiac dimensions over 5 years in highly trained long-distance runners and sprinters - Calder, F. J.; Diaz, V.; Peinado, A. B.; Benito, P. J.; Maffulli, N. (The Physician and Sportsmedicine, 2010)
Aims We assessed the changes in cardiac morphology between elite endurance-trained runners (n = 42) and elite sprinters (n = 34) over a 5-year period. In addition, we studied the relationship between heart size and maximum oxygen consumption (VO2 max). Methods At the beginning of 5 consecutive seasons, all athletes underwent an incremental running test to determine VO2 max and a color-coded pulsed Doppler examination to determine baseline echocardiographic variables. We hypothesized that cardiac morphology had reached its upper limit in elite athletes, and showed only minor changes during 5 years of regular training. Results Although all echocardiographic variables remained stable in nearly all sprinters studied, in the endurance runners (who presented higher cardiac cavity dimensions compared with sprinters), variations in heart morphology became evident from the third season, and were within established physiological limits. Conclusion Only 6 (17%) endurance runners and 3 (9%) sprinters showed a left ventricular internal diameter of > 60 mm (the threshold pathological value) at end diastole at some point during the observational period. Moreover, no statistically significant association was detected between changes in VO2 max and changes in heart size. After 5 years of intense training, the changes of the echocardiographic variables examined remained different between endurance runners and sprinters.